Метод увеличения быстродействия устройства грозозащиты приёмников радиотехнических и телекоммуникационных систем - Шостко, И. С. (ХНУРЭ, 2011)
A new method for increasing the speed of spark gap protects the receiver telecommunication systems by preionization discharge gap of infrared laser light.
Keywords: радиотехнические системы; эффективность телекоммуникационных систем